2019
DOI: 10.1002/cam4.2281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of neutrophil‐to‐lymphocyte ratio and platelet‐to‐lymphocyte ratio for breast cancer patients: An updated meta‐analysis of 17079 individuals

Abstract: Aims This study aimed to evaluate the prognostic effect of neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) for patients with breast cancer (BC). Methods A literature search was performed by searching medical databases. Basic characteristics and prognostic data were extracted from included studies. Primary outcomes, such as overall survival (OS) and disease‐free survival (DFS), were synthesized and compared. Subgroup analyses were performed ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 59 publications
5
129
2
2
Order By: Relevance
“…Studies have confirmed that the pretreatment platelet-to-lymphocyte ratio is related to the prognosis of a variety of malignant tumors, including hepatocellular carcinoma, colorectal cancer, breast cancer, etc. [24][25][26] Unfortunately, no prognostic value was found in our study. Albumin and globulin are two major components of serum protein, which play important roles in the inflammatory process.…”
Section: Discussioncontrasting
confidence: 77%
“…Studies have confirmed that the pretreatment platelet-to-lymphocyte ratio is related to the prognosis of a variety of malignant tumors, including hepatocellular carcinoma, colorectal cancer, breast cancer, etc. [24][25][26] Unfortunately, no prognostic value was found in our study. Albumin and globulin are two major components of serum protein, which play important roles in the inflammatory process.…”
Section: Discussioncontrasting
confidence: 77%
“…Systemic inflammation could be monitored by using peripheral hematologic markers, such as neutrophils, leukocytes and platelets. Based on the relationship between inflammation and cancer, in recent years, inflammatory marker-based scores, such as NLR and PLR have been reported to be associated with the prognosis of patients with various cancers, including lung cancer [8], breast cancer [10,23], gastric cancer [11,24] and colorectal cancer [25]. However, NLR and PLR only include two types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…12 A great deal of studies have indicated that the inflammatory markers, such as white blood cell (W), neutrophil (N), monocyte (M), platelet (P), lymphocyte (L), as well as neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), platelet to lymphocyte ratio (PLR), and systemic immune-inflammation index (SII), are present and detectable in the systemic circulation, and have been widely proposed as prognostic factors for many malignancies. [13][14][15][16] A novel and integrated indicator that named Systemic Inflammation Response Index (SIRI), which is based on neutrophil (N), monocyte (M), and lymphocyte (L) counts, is reported to be associated with clinical outcomes and predict the survival of patients with gastric cancer. 17 This integrated indicator may comprehensively reflect the balance of host immune and inflammatory status compared with NLR, LMR, and PLR.…”
Section: Introductionmentioning
confidence: 99%